Characterization of plaque variants and the involvement of Quasi-Species in a population of EV-A71 - Mandary, M. B. *; Masomian, Malihe *; Ong, Seng Kai *; Poh, Chit Laa * (MDPI, 2020)
Viral plaque morphologies in human cell lines are markers for growth capability and they have been used to assess the viral fitness and selection of attenuated mutants for live-attenuated vaccine development. In this study, we investigate whether the naturally occurring plaque size variation reflects the virulence of the variants of EV-A71. Variants of two different plaque sizes (big and small) from EV-A71 sub-genotype B4 strain 41 were characterized. The plaque variants displayed different in vitro growth kinetics compared to the parental wild type. The plaque variants showed specific mutations being present in each variant strain. The big plaque variants showed four mutations I97L, N104S, S246P and N282D in the VP1 while the small plaque variants showed I97T, N237T and T292A in the VP1. No other mutations were detected in the whole genome of the two variants. The variants showed stable homogenous small plaques and big plaques, respectively, when re-infected in rhabdomyosarcoma (RD) and Vero cells. The parental strain showed faster growth kinetics and had higher viral RNA copy number than both the big and small plaque variants. Homology modelling shows that both plaque variants have differences in the structure of the VP1 protein due to the presence of unique spontaneous mutations found in each plaque variant This study suggests that the EV-A71 sub-genotype B4 strain 41 has at least two variants with different plaque morphologies. These differences were likely due to the presence of spontaneous mutations that are unique to each of the plaque variants. The ability to maintain the respective plaque morphology upon passaging indicates the presence of quasi-species in the parental population.